Characterization of nano-sized CdS-Ag2S core-shell nanoparticles using XPS technique - Hota, G.; Idage, Susheela B.; Khilar, Kartic C. (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2007)
This paper reports the use of X-ray photoelectron spectroscopy (XPS) method for the characterization of surface composition of core and shell nanoparticles. The core and shell nanoparticles were synthesized using sodium bis(2-ethylhexyl) sulfosuccinate (AOT)/n-heptane/water microemulsion technique. The post-core and partial microemulsion methods have shown promise for core and shell formation and enhanced stability and sphericity of the semiconductor nanoparticles. In addition to above technique, the core-shell nanoparticles have also been characterized using SEM-elemental detection X-ray analysis (EDAX) and results are discussed. The XPS studies of US, Ag2S, and CdS-Ag2S nanoparticles prepared by post-core/partial microemulsion methods were carried out and results are compared with physical mixing of US and Ag2S nanoparticles. The Ag/Cd atomic ratio is found to be 5 and 10 as determined by XPS methods for nanoparticles prepared by using post-core and partial microemulsion methods, respectively. These results show the formation of core and shell nanoparticles. (c) 2006 Elsevier B.V. All rights reserved.

New poly(phenylene oxide)/polystyrene blend nanocomposites with clay: intercalation, thermal and mechanical properties - Tiwari, Rajkiran R.; Khilar, Kartic C.; Natarajan, Upendra (Journal of Applied Polymer Science, 2008)
We present the first study and results on the preparation and characterization of montmorillonite clay filter based polymer blend nanocomposites of the miscible poly(phenylene oxide)/polystyrene blend. Intercalated nanocomposites, prepared by a melt-processing method with 2-6 wt % commercially available organically modified sodium montmorillonite, have been characterized with wide-angle X-ray diffraction, transmission electron microscopy analysis, thermal analysis (thermogravimetric analysis and differential scanning calorimetry), and mechanical tensile tests. We show that nanocomposites can be successfully prepared in a batch mixer at temperatures much below the conditions conventionally used for this blend without organic degradation. Thermal stability is enhanced by nanoscale hybrid formation. The level of intercalation (change in the d-spacing) does not change with the clay loading. Better dispersion of clay in the blend matrix has been observed at a low level of clay content. The nanocomposites show improved tensile modulus (by 31%) in comparison to the blend, whereas the tensile strength (stress at break) and elongation decrease in the presence of the filler with an increase in the clay loading. The Halpin-Tsai model is able to predict the modulus of the nanocomposites in very good agreement with the experimental data. (c) 2008 Wiley Periodicals, Inc.
Keywords: mechanical properties; Nanocomposites; organoclay; poly(phenylene oxide); Polystyrene; Thermal properties

Synthesis and characterization of novel organo-montmorillonites - Tiwari, Rajkiran R.; Khilar, Kartic C.; Natarajan, Upendra (Applied Clay Science, 2008)
Sodium Montmorillonite (NaMMT) has been modified via cation exchange reaction using three different organic cations. Basal spacings, interlamellar structure and thermal stability of these organo-montmorillonites (OMMT) clays have been characterized using wide angle X-ray diffraction (WARD) and thermogravimetric analysis (TGA) techniques. Increase in the basal spacing due to organic modification is in good agreement with simple theoretical calculations based on van der Waals volume of the cationic ammonium ions. TGA characterization and analysis show that the amount of organic modifier in the OMMT's is in good agreement with theoretically calculated stoichiometric content expected for almost complete exchange of Na+ ions by organic cations. The OMMT's shows stepwise decomposition corresponding to initial weight loss from residual water desorption, followed by decomposition of the organic surfactant and the dehydroxylation of structural water of the montmorillonite layers. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Montmorillonite; organo-clays; organo-montmorillonite; surfactant